A method for optimizing hydrogel structure and fracture performance
By constructing a weak interface with a vertical or symmetrical arrangement in the hydrogel, changing the development direction of the initial crack, solving the complexity and non-universality of hydrogel fracture performance optimization in the prior art, and achieving structural performance Lifting and stress-reducing effects.
Patent Information
- Application Number
- CN202410036457.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-01-10
AI Technical Summary
When improving the fracture performance of hydrogels, the prior art mainly relies on changing the components. The preparation process is complex and lacks universality, making it difficult to effectively optimize fracture performance from the structural level.
By constructing the development end of the I-type initial crack in the hydrogel, artificially introduces a weak interface arranged vertically or symmetrically, changing the development direction of the crack, reducing the initial crack propagation resistance, and guiding the crack to develop towards the weak interface, thereby improving fracture performance.
It has achieved the structural improvement of hydrogel fracture performance, strong operability, and is suitable for isotropic hydrogels. It can significantly improve fracture performance for existing cracks or defect-free hydrogels and reduce stress concentration.
Smart Images

Figure CN117942883B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of engineering materials, and in particular relates to a hydrogel structure and a fracture performance optimization method. Background Art
[0002] Hydrogel is a type of elastomeric material that can be used in different fields. The mechanical properties of hydrogel are the key indicators that determine its use, and among the mechanical properties, fracture performance is an important component. In addition to trying to hinder the expansion of cracks, existing technical means to improve the fracture performance of hydrogels also include guiding the direction of crack deflection and improving the performance of the structure. However, the above-mentioned crack deflection technology is mainly achieved by changing the composition of the hydrogel, that is, preparing or improving the fracture performance of the hydrogel from a microscopic perspective. Specifically, deflecting the molecular chain from a microscopic structure can achieve the purpose of deflecting cracks, but it is necessary to prepare a hydrogel with anisotropic properties. The preparation process of such anisotropic hydrogels is relatively complicated, and has special requirements for the synthetic materials used, and is not universal. Summary of the invention
[0003] In a first aspect, the present invention provides a hydrogel structure, which is conceived from a macroscopic perspective to eliminate the influence of initial defects of the hydrogel and optimize the fracture performance of the hydrogel.
[0004] The specific technical solutions are as follows:
[0005] A hydrogel structure, wherein the hydrogel has an I-type initial crack, the initial crack has a development end that can continue to expand into the hydrogel structure, the development end is provided with a weak interface extending into the hydrogel structure, and the weak interface is used to guide the development direction of the initial crack.
[0006] Furthermore, the initial crack has a starting end where the crack begins to expand, the path between the starting end and the development end is the initial crack path, the extension path of the weak interface is the weak interface path, the weak interface is located on one side of the initial crack and the weak interface path is perpendicular to the initial crack path.
[0007] Furthermore, the initial crack has a starting end where the crack begins to expand, the path between the starting end and the development end is the initial crack path, the extension path of the weak interface is the weak interface path, the weak interface is symmetrically arranged on both sides of the initial crack along the initial crack path, and the weak interface paths are perpendicular to the initial crack path.
[0008] Furthermore, the hydrogel is in the shape of a thin plate, and the initial crack path is along the length direction of the hydrogel.
[0009] Furthermore, the initial crack is located at the center line of the longitudinal section of the hydrogel.
[0010] Furthermore, the hydrogel is isotropic.
[0011] In a second aspect, the present application provides a method for optimizing the fracture performance of a hydrogel, comprising the following steps:
[0012] A weak interface is constructed at the development end of a type I initial crack of a hydrogel having an isotropic property, and an extension direction of the weak interface is perpendicular to the development direction of the initial crack.
[0013] In a third aspect, the present application provides a method for optimizing the fracture performance of a hydrogel, comprising the following steps:
[0014] An initial crack of type I is constructed in a defect-free hydrogel structure having isotropic properties, and two weak interfaces are symmetrically constructed at the developing end of the initial crack and in a direction perpendicular to the initial crack.
[0015] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows:
[0016] 1. This application is different from the traditional method of improving the fracture performance of hydrogels from the chemical component level. The hydrogel structure designed in this application improves the fracture performance of hydrogels from the structural level. It is highly operational and extensible, and can be applied to different types of isotropic hydrogels.
[0017] 2. The first hydrogel fracture performance optimization method proposed in this application can improve the fracture performance of hydrogels with existing cracks. Specifically, after setting a weak interface, the weak interface will reduce the extension resistance of the initial crack to the part where the weak interface is located, thereby guiding the initial crack to develop to one side of the weak interface, thereby changing the process of development along the initial crack path, and finally improving the fracture performance of the hydrogel.
[0018] 3. The second hydrogel fracture performance optimization method proposed in the application can improve the fracture performance of defect-free hydrogels. After constructing the initial crack at a specific location, a vertical weak interface is constructed at the development end of the initial crack. The weak interface can be arranged on one side or both sides of the initial crack. When arranged on both sides, the stress concentration phenomenon of the initial crack during the development process will be significantly weakened, thereby eliminating the influence of the initial defect and improving the fracture performance of the hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0020] Figure 1 A schematic diagram of the hydrogel structure provided in this application;
[0021] Figure 2 It is a schematic diagram of the test results of Example 1;
[0022] Figure 3 It is a schematic diagram of the test results of Example 2;
[0023] Figure 4 This is a schematic diagram of the test results of Example 3;
[0024] Figure 5 This is a schematic diagram of test results of the present application in one implementation mode;
[0025] Figure 6 This is a schematic diagram of the test results of Example 4;
[0026] Figure 7 This is a schematic diagram of the test results of Example 5;
[0027] Figure 8 This is a schematic diagram of the test results of Example 6;
[0028] In the attached figure, 1, hydrogel; 2, initial crack; 3, weak interface; 4, development end; 5, starting end. DETAILED DESCRIPTION
[0029] Based on the background technology, as shown in the attached Figure 1 As shown, a hydrogel structure, the hydrogel 1 has an initial crack 2 of type I, the initial crack 2 has a development end 4 that can continue to expand into the hydrogel structure, the development end 4 is provided with a weak interface 3 extending into the hydrogel structure, and the weak interface 3 is used to guide the development direction of the initial crack 1.
[0030] Terminology explanation:
[0031] Type I crack, also known as opening crack, is a type of crack formed when the crack surface produces an opening displacement under the action of tensile stress orthogonal to the crack surface.
[0032] Weak interface: A weak interface artificially constructed to meet the need for crack expansion along the weak interface direction. Its interface debonding energy is much smaller than the fracture energy of the hydrogel.
[0033] The weak interface 3 of the present application is different from the traditional existence of weak interfaces. The weak interface 3 of the present application is prefabricated and formed by human intervention, and its implementation effect is predictable in the present application.
[0034] The principle of introducing a weak interface is as follows: In an isotropic material, the "thrust" for the initial crack to expand is the energy release rate, and the "resistance" that prevents the initial crack from expanding is the fracture energy. The energy release rate of the initial crack developing in each direction is different, but the fracture energy is the same. When a hydrogel with an initial type I crack is subjected to a pure shear test, the initial crack will expand in a straight line. After the weak interface is introduced, the "resistance" of the hydrogel in the direction of the weak interface is weakened, and the initial crack will tend to develop toward the hydrogel on the weakened side, thereby changing the development path of the initial crack, reducing the stress concentration phenomenon, and achieving a self-reinforcement effect.
[0035] The angle between the weak interface path and the initial crack path will affect the performance improvement effect. The present application does not specifically limit the angle formed by the weak interface path and the initial crack path, and it can adopt any one of the following embodiments:
[0036] Embodiment 1:
[0037] The hydrogel sheet model was established using Abaqus finite element software. The length of the sheet is L = 50 mm, the height is H = 10 mm, the thickness of the sheet is d = 0.1 mm, the length of the prefabricated crack is a = 20 mm, and the shear modulus is =5.614kpa, the material is defined using the neo-Hookean model. The material parameters obtained through the experiment are: hydrogel critical fracture tensile =1.62, fracture energy =32J / m 2 First, a pure shear test was performed on the defect-free hydrogel to obtain the G- Relationship (G is defined as the energy required per unit area for crack extension, The critical tensile strength of the hydrogel with type I initial crack is calculated by using cohesive contact and vusdfle subroutine to simulate the fracture of the hydrogel. , the critical tensile strength Substitute the G- Relationship determines fracture toughness, critical fracture tensile The corresponding energy release rate G That is the fracture toughness.
[0038] The simulation results and errors are shown in Table 1.
[0039] Table 1 Simulation results and error table
[0040]
[0041] The vusdfle subroutine is used to define the horizontal expansion of the damage control crack of the material. At the crack development end, cohesive contact is used to connect the left part above the crack with the right part in the vertical direction to simulate the effect of the prefabricated weak interface in actual conditions. By changing the fracture energy of the cohesive contact, the crack expansion path can be changed. In order to speed up the finite element calculation process, the following embodiment uses the vusdfle subroutine to control the critical fracture tensile test of the hydrogel with type I initial crack without prefabricated weak interface in pure shear test =1.2.
[0042] As attached Figure 2 As shown in the figure, the weak interface path of this embodiment is 45° to the initial crack path. The fracture energy of the weak interface set in Abaqus is weak enough to ensure that the crack will first expand along the weak interface direction. The test results are shown in the attached figure. Figure 5 shown.
[0043] According to the attached Figure 5 It can be seen that the crack peels off the material along the preset interface direction, while also weakening the sharpness of the crack tip and alleviating the impact of stress concentration, but it destroys the integrity of the hydrogel on the right to a certain extent, causing damage to the upper edge of the hydrogel on the right.
[0044] Embodiment 2:
[0045] The only difference between this embodiment and the first embodiment is that the weak interface path is 135° away from the initial crack path. As the crack expands along the preset weak interface direction, the sharpness of the crack tip is deepened, the stress concentration phenomenon is enhanced, and the structure is fractured prematurely.
[0046] As a preferred embodiment of the above embodiment:
[0047] The initial crack has a starting end where the crack begins to expand, the path between the starting end and the development end is the initial crack path, the extension path of the weak interface is the weak interface path, the weak interface is located on one side of the initial crack and the weak interface path is perpendicular to the initial crack path.
[0048] Embodiment three:
[0049] As attached Figure 4 As shown, the difference between this embodiment and the first embodiment is that the weak interface path and the initial crack path are at 90°.
[0050] The initial crack extends along the preset weak interface direction, which weakens the sharpness of the crack tip and reduces the impact of stress concentration. At the same time, it also protects the integrity of the right part and improves the critical fracture tensile strength and fracture toughness of the structure.
[0051] The test results of various angles under this embodiment are shown in the attached figure. Figure 5 As shown, the effect is relatively better when the weak interface is loaded along the initial direction.
[0052] As a preferred embodiment of the present application, the initial crack has a starting end 5 where the crack begins to expand, the path between the starting end 5 and the development end 4 is the initial crack path, the extension path of the weak interface 3 is the weak interface path, the weak interface 3 is symmetrically arranged on both sides of the initial crack 2 along the initial crack path, and the weak interface paths are perpendicular to the initial crack path.
[0053] As a preferred embodiment of the present application, the hydrogel is in the shape of a thin plate, and the initial crack path is along the length direction of the hydrogel.
[0054] The length of the weak interface will affect the fracture toughness of the overall structure. The present application does not limit the specific hydrogel structure. The weak interface and the hydrogel can adopt any one of the following embodiments:
[0055] Embodiment 4:
[0056] As attached Figure 6 As shown in FIG. 1 , the ratio of the length of the weak interface to the height of the hydrogel in this embodiment is 0.1. Figure 6 It can be seen that the prefabricated weak interface is too short to weaken the sharpness of the crack tip, but instead strengthens it, causing the structure to break prematurely.
[0057] Embodiment five:
[0058] As attached Figure 7 As shown, the only difference between this embodiment and embodiment 4 is that the ratio of the length of the weak interface to the height of the hydrogel is 0.3. As the length of the prefabricated weak interface increases, as the crack propagates along the weak interface, the sharpness of the crack tip is weakened, the influence of stress concentration is reduced, and the fracture toughness of the structure under fracture tensile stress is improved.
[0059] Embodiment six:
[0060] As attached Figure 8 As shown, the only difference between this embodiment and the fourth embodiment is that the ratio of the length of the weak interface to the height of the hydrogel is 0.5, and the initial crack will peel off the material along the direction of the weak interface. At this time, the effect of improving the fracture performance of the hydrogel is the best.
[0061] As a preferred embodiment of the present application, the initial crack is located at the center line of the longitudinal section of the hydrogel. The initial crack at the center line helps to peel the material to both sides, which can greatly improve the performance optimization effect.
[0062] As a preferred embodiment of the present application, the hydrogel is isotropic. In an isotropic material, the fracture energy is the same along the crack propagation direction, and the implementation effect is better.
[0063] The present application also provides a method for optimizing the structure of a hydrogel. Specifically, a weak interface is constructed at the development end of a type I initial crack of a hydrogel with isotropic properties, and the extension direction of the weak interface is perpendicular to the development direction of the initial crack.
[0064] The specific steps are: place the cured hydrogel with a silicone rubber spacer into a mold consisting of two glass plates and another silicone rubber spacer. The middle mold is used to separate and create a weak interface. Pour the uncured hydrogel solution into the mold, add the curing agent, and put it in an oven to cure the hydrogel. Adjusting the concentration of the curing agent can adjust the interface debonding energy, and reducing the concentration of the curing agent can obtain a weaker interface.
[0065] Another method of optimizing the hydrogel structure of the present application is to construct a type II initial crack in a defect-free hydrogel structure having isotropic properties, and construct one or two weak interfaces at the development end of the initial crack in a direction perpendicular to the initial crack. The type II initial crack can further improve the fracture performance, and the initial crack can develop evenly in the upper and lower parts, significantly improving the fracture performance.
[0066] Anything not described in this application can be achieved by adopting or drawing on existing technologies.
[0067] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A hydrogel structure, characterized in that: The hydrogel has an I-type initial crack, the initial crack has a development end that can continue to expand into the hydrogel structure, the development end is provided with a weak interface extending into the hydrogel structure, the weak interface is used to guide the development direction of the initial crack; the interface debonding energy of the weak interface is much smaller than the fracture energy of the hydrogel, and the manufacturing steps are as follows: The cured hydrogel with a silicone rubber spacer is placed in a mold consisting of two glass plates and another silicone rubber spacer. The middle mold is used to separate and create a weak interface. The uncured hydrogel solution is poured into the mold, and then a curing agent is added. The hydrogel is placed in an oven to cure the hydrogel. Adjusting the concentration of the curing agent can adjust the interface debonding energy, and reducing the concentration of the curing agent can obtain a weaker interface.
2. A hydrogel structure according to claim 1, characterized in that: The initial crack has a starting end where the crack begins to expand, the path between the starting end and the development end is the initial crack path, the extension path of the weak interface is the weak interface path, the weak interface is located on one side of the initial crack and the weak interface path is perpendicular to the initial crack path.
3. A hydrogel structure according to claim 1, characterized in that: The initial crack has a starting end where the crack begins to expand, the path between the starting end and the development end is the initial crack path, the extension path of the weak interface is the weak interface path, the weak interface is symmetrically arranged on both sides of the initial crack with respect to the initial crack path, and the weak interface paths are perpendicular to the initial crack path.
4. A hydrogel structure according to claim 2 or 3, characterized in that: The hydrogel is in the shape of a thin plate, and the initial crack path is along the length direction of the hydrogel.
5. A hydrogel structure according to claim 4, characterized in that: The initial crack is located at the center line of the longitudinal section of the hydrogel.
6. A hydrogel structure according to claim 5, characterized in that: The hydrogel is isotropic.
7. A method for optimizing the fracture performance of a hydrogel, characterized in that: The following steps are involved: Constructing a weak interface at the development end of a type I initial crack of a hydrogel having an isotropic property, wherein the extension direction of the weak interface is perpendicular to the development direction of the initial crack; The interfacial debonding energy of the weak interface is much smaller than the fracture energy of the hydrogel, and the preparation steps are as follows: The cured hydrogel with a silicone rubber spacer is placed in a mold consisting of two glass plates and another silicone rubber spacer. The middle mold is used to separate and create a weak interface. The uncured hydrogel solution is poured into the mold, and then a curing agent is added. The hydrogel is placed in an oven to cure the hydrogel. Adjusting the concentration of the curing agent can adjust the interface debonding energy, and reducing the concentration of the curing agent can obtain a weaker interface.
8. A method for optimizing the fracture performance of a hydrogel, characterized in that: The following steps are involved: Constructing an initial crack of type I in a defect-free hydrogel structure having isotropic properties, and symmetrically constructing two weak interfaces at the development end of the initial crack and in a direction perpendicular to the initial crack, wherein the interface debonding energy of the weak interfaces is much smaller than the fracture energy of the hydrogel; The production steps are as follows: The cured hydrogel with a silicone rubber spacer is placed in a mold consisting of two glass plates and another silicone rubber spacer. The middle mold is used to separate and create a weak interface. The uncured hydrogel solution is poured into the mold, and then a curing agent is added. The hydrogel is placed in an oven to cure the hydrogel. Adjusting the concentration of the curing agent can adjust the interface debonding energy, and reducing the concentration of the curing agent can obtain a weaker interface.
Citation Information
Patent Citations
Preparation and application of high strength anti-tear magnetic hydrogel
CN105175970A
Hydrogel-forming polymeric material with desirable fracture properties
CN1121082A
Manufacturing method of PVA hydrogel, and manufacturing method of PVA hydrogel laminate
JP2015004059A
